Development of expert recommendations for the treatment of PTSD with comorbid substance use disorder. Issue 1 (1st February 2021) - Roberts, Neil P.
Abstract: Background : PTSD and substance use disorder (SUD) frequently co-occur. Estimates of life time PTSD amongst SUD patients range from 26% to 52%, with estimates of current PTSD between 15% and 42%. Amongst individual diagnosed with PTSD estimates of comorbid substance abuse range from 19% to 35% and comorbid alcohol abuse from 36% to 52% (Roberts, Roberts, Jones, & Bisson, 2016 ). PTSD-SUD comorbidity presents many clinical challenges for treating clinicians. Individuals with PTSD-SUD present with a more severe clinical profile, tend to have poorer functioning and wellbeing, and inferior treatment outcomes. Clinicians view this comorbidity to be substantially more difficult to treat than either disorder alone (Schäfer & Lotzin, 2018 ). There are now a number of well-established psychological therapies for PTSD. These include prolonged exposure, cognitive therapy, cognitive processing therapy and EMDR (Bisson et al., 2019 ). However, patients with PTSD-SUD comorbidity are often excluded from clinical trials of psychological intervention. Clinicians are therefore often uncertain about how best to implement effective treatment, and traditionally, patients with this comorbidity have been offered treatment sequentially. This normally involves referral for to PTSD treatment only after completion of treatment for addiction (Roberts, Back, Mueser, & Murray, 2020 ). However, there are concerns about whether this approach causes some patients to 'fall through the cracks' between services and there is debate about whether integrated or simultaneous approaches might be more effective. A number of integrated treatment approaches have been developed. These are often grouped into past focused treatments, which include components of exposure-based trauma processing; and present focused treatments, which focus more on improving current coping skills (see Roberts et al., 2020 ). Recent reviews have tended to report more support for exposure-based approaches, particularly in relation to PTSD outcomes (Roberts et al., 2020 ), although findings have been based on a small number of studies and high drop-out from treatment has been noted as a problem across different approaches. Most recent guidelines (e.g. ISTSS 2018 – see NICE 2018 ; Bisson et al., 2019 ) have not included scoping questions to address issues of comorbidity, and there are no widely accepted guidelines about how to deliver optimal care and treatment for such individuals. Objectives and methodology : To describe the work of a task force which has been established to develop expert recommendations for the psychological treatment of this comorbidity for ESTSS, following principles used in guideline development through two stages. Stage 1 . Update of a systematic review and meta-analysis (Roberts et al., 2016 ) of RCTs of psychological interventions aimed at treating comorbid PTSD and SUD, with the aim of establishing the current evidence base for a number of approaches including: Trauma focused CBT trauma focused treatments plus treatment as usual for SUD, such as COPE Present focused treatments such as Seeking Safety plus treatment as usual for SUD Integrated cognitive restructuring-based interventions plus treatment as usual for SUD EMDR plus treatment as usual for SUD. The working group also seeks to investigate whether there is evidence for different models of treatment delivery: i.e. sequential treatments, vs. integrated treatments delivered by the same therapist vs simultaneous treatments delivered by different therapists. Treatment recommendations will be based on the strength and quality of the findings addressing which will be evaluated through the GRADE approach. Stage 2 . It is anticipated that many of the challenges faced in clinical practice are unlikely to be addressed through the Stage 1 process, where there is limited high-quality evidence to make evidence-based recommendations. Stage 2 will involve the collation good practice/consensus point recommendations made in trusted methodologically rigorous treatment guidelines and expert guidance publications. Findings and Recommendations : This project is currently ongoing. The presentation will provide an update of the progress of the working group, share preliminary findings where these are available and make recommendations for future research.